Uma analise do processo de privatização brasileiro, com enfase no setor siderurgico - Braga, Ana Cristina Gazolla (1996)
The Brazilian 'entrepreneurial state' model began to fail at the early eighties since then we notice the beginning of a big technological gap betwen the state-owned industrial sector versus its competitors in the private sector. Due to that the govemment took the decision that it would be necessary to transfer the control of its companies to the private sector, in order to attend their growing investment needs. The framework of this new policy was structured under the Brazilian Pivatization Program, launched during Mr. Fernando Collor govemment. The Program has been continued during Mr. Itamar Franco and Mr. Fernando Henrique Cardoso govemments as well. In spite of a certain leveI of opposition that arose during the implementation of the Program, many positive goals were achieved due to the privatization of several stateowned companies. One of the main goals of the Privatization Program is the decrease of the Public Sector overall debt. This goaI matches with the govemment efforts to restructure its own finances, which imply the decrease of its public overaIl expenditures. This analysis makes an evaluation of the Brazilian Privatization from its beginning in 1990 until 1995. The goat set by the program was to privatize 74 state-owned companies, during this period 41 companies have been priatized. This total includes the saIe of companies owned by Petroquisa and Petrofertil from the Brazilian Petrochemical sector. The Steel sector was the first to be privatized as a whole. In this analysis we made a report ofthe privatization ofUsiminas and Acesita, which became well-known samples of privatization and has been achieving outstanding results under its new private management. The anaIyses ofUsiminas and Acesita privatization was focused on the preparation steps for their sale, its financial position prior to the sale, the auction process and the results achieved at the end of the processo In addition, it was developed an analysis of the main problems faced by the Steel Sector prior to the privatization, as well as one has demonstrated the importance of the privatization of these companies for the overcoming of these problems.